Pengaruh Iklim Organisasi dan Stres Kerja terhadap Pelaksanaan Kesehatan dan Keselamatan Kerja (K3) dengan Motivasi Kerja sebagai Variabel antara di PT. POSCO Indonesia Jakarta Processing Center - Veviet Leli Istianovi (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Technological advances in the industry make companies use a variety of tools and machines to facilitate the work, but in practice the interaction between humans and machines often lead to accidents. The working environment is safe and comfortable is required by workers to increase productivity and achieve its goals. The purpose of this study is to identify and explain the effect of Climate Organization (X1), Job Stress (X2) and work motivation (Z) of the Implementation of the Health and Safety Executive (Y). Data were analyzed using Structural Equation Model (SEM) to describe the relationship between latent variables with the indicators and to describe the relationship between latent variables. After testing and data analysis of the obtained conclusions on the direct effects between variables as follows: X1 significantly affect Y of 3.61%; X2 significantly affect Y of 5.29%; X1 significantly influence Z of 20.25%; X2 significantly influence Z of 6.25%; and Z significantly influence Y by 67.24%. As for the indirect effect obtained the following conclusions: X1 significantly affect Y through Z of 13.69%; and X2 significantly influence Y by Z at 4%.